Dynamics Of Waste Governance Policy In Pekanbaru: A Literature Review On The Transition From Outsourcing Model To Regional Public Service Agency (BLUD) - Zulkarnaini Zulkarnaini; Nadila Saumitri; Icha Octavia (Science and Education Journal (SICEDU), 2026)
Urban waste management represents a persistent governance challenge in rapidly urbanizing Indonesian cities. This study examines the policy dynamics of waste governance in Pekanbaru City through a systematic literature review, focusing on the institutional transition from a third-party outsourcing model to the establishment of a Regional Public Service Agency (Badan Layanan Umum Daerah/BLUD). Employing a descriptive-analytical qualitative approach, data were drawn from government regulations, planning documents, academic journals, and institutional reports. The findings reveal that waste management failures in Pekanbaru constitute fundamentally governance failures rather than technical deficiencies, characterized by weak oversight mechanisms, contractual imbalances, and persistent implementation gaps. The outsourcing model demonstrated structural vulnerabilities including service disruptions, labor conflicts, and insufficient public accountability. In response, the city government has initiated BLUD formation, a post-NPM institutional reform offering greater operational flexibility and enhanced accountability. Comparative evidence suggests BLUD can effectively integrate circular economy principles into urban waste governance, provided it is supported by disciplined internal management, competent human resources, and robust multi-stakeholder coordination. This study contributes to theoretical discourses on public policy implementation, environmental governance, and institutional reform in developing cities.